Relevansi Ijma’ Dan Qiyas Dalam Struktur Hukum Islam Dan Struktur Hukum Positif Di Indonesia - Balya, Deden Ibnu (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2019)
Abstract The concept of ijma ', and its relevance in construction and improvisation of Islamic law is part of the Islamic law studies, which can always develop according to place and time, time in terms of times and regions in the sense of the state. Ijma', of course functions as a tool for taking legal conclusions, both those whose sources are divine and the sunnah of the Prophet Muhammad PBUH. This paper is qualitative writing, with library research methods, with primery data is sources of books and legal nomenclature, and using the descriptive analysis. Based on the analysis, it is known that the level of relevance of ijma as a method, till nowaday, its relevance is still very high, especially with the region and the spread of Islam that is indeed cross-country, cross-nation, and across cultures. Ijma 'of the ulama becomes very important, because in addition to being a response to the development of the times, ijma' also remains a necessity for Muslims, considering that not everyone is able to do istinbaht / legal conclusions in Islam. Keywords : Ijma’ and Qiyas, Source of Islamic Law, Legal Development.